2020
DOI: 10.1155/2020/6283754
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Roles of hα-syn (A53T) in the Pathogenesis of Parkinson’s Disease: Synaptic Pathology and Neuronal Aging

Abstract: The motor and nonmotor symptoms of PD involve several brain regions. However, whether α-syn pathology originating from the SNc can directly lead to the pathological changes in distant cerebral regions and induce PD-related symptoms remains unclear. Here, AAV9-synapsin-mCherry-human SNCA (A53T) was injected into the unilateral SNc of mice. Motor function and olfactory sensitivity were evaluated. Our results showed that AAV9-synapsin-mCherry-human SNCA was continuously expressed in SNc. The animals showed mild m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…It has been reported that α-synuclein accumulation reduces GABAergic inhibitory transmission in a model of multiple system atrophy 41 . Consistent with our findings, a recent study found that α-synuclein aggregation induced a reduction in presynaptic membrane area 5 , likely due to binding of α-synuclein aggregates with microtubule beta-III to form an insoluble complex. This complex may also regulate release of synaptic vesicles in GABAergic interneurons 41 .…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that α-synuclein accumulation reduces GABAergic inhibitory transmission in a model of multiple system atrophy 41 . Consistent with our findings, a recent study found that α-synuclein aggregation induced a reduction in presynaptic membrane area 5 , likely due to binding of α-synuclein aggregates with microtubule beta-III to form an insoluble complex. This complex may also regulate release of synaptic vesicles in GABAergic interneurons 41 .…”
Section: Discussionsupporting
confidence: 93%
“…Typically, changes in the amplitude of mini postsynaptic currents represent alterations in postsynaptic effects, whereas frequency changes are largely due to the release of presynaptic neurotransmitters. It has been reported that α-synuclein deposits can induce structural and functional damage in the presynaptic area [ 36 39 ]. We thus assessed the factors influencing presynaptic effects, including the overall interneurons and the complex synaptic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of aggregated and insoluble S129 phosphorylated α-synuclein in these mice follows a similar accumulation as that observed in humans with synucleinopathy. Reactive gliosis and mitochondrial alterations are also evident in various brain regions, along with synaptic dysfunction in the hippocampus, which may contribute to cognitive deficits [ 39 , 40 ]. These mice were bred on a C57BL/C3H background to produce transgenic homozygous and wildtype littermates.…”
Section: Methodsmentioning
confidence: 99%